Low Cost Non-Destructive Monitoring of Dry Milling Process of Ilmenite Material Using Acoustic Sound Wave to Support Industry 4.0 - Handoko Setyo Kuncoro; Dadan Sumardan (Balai Besar Keramik, 2020)
The potential utilization and characteristics of acoustic sound waves in the frequency range of 100-10000 Hz for the monitoring process of dry milling of industrial ilmenite materials are evaluated based on the evolution of sound intensity level and the number of peaks in the spectrumwaves.The methodology in this applicative research follows the steps of material preparation activities, dry milling process, acoustic milling emission monitoring, particle size shieving / filtering, quantization of particle size distribution and evaluation of research data.The milling times from 0.5, 15 to 30 hours are taken as a variation of the study. Statistical ANOVA evaluation results show a significant relationship between milling time and the characteristics of the peak number of acoustic wave emited milling process.Higher color gradient in the evolution plot of the frequency spectrum between 160-640 Hz decreases with increasing milling time and decreasing particle size distribution.The number of spectral peaks also increases with increasing milling time.This indicates the effectiveness of collision by alumina balls in the processed ilmenite material using dry milling and has potential implications for the use of a more controlled and efficient ball mill in the future of ceramic industry.